2019
DOI: 10.1177/0003702819858671
|View full text |Cite
|
Sign up to set email alerts
|

Key Role of Cytochrome C for Apoptosis Detection Using Raman Microimaging in an Animal Model of Brain Ischemia with Insulin Treatment

Abstract: Brain ischemia represents a leading cause of death and disability in industrialized countries. To date, therapeutic intervention is largely unsatisfactory and novel strategies are required for getting better protection of neurons injured by cerebral blood flow restriction. Recent evidence suggests that brain insulin leads to protection of neuronal population undergoing apoptotic cell death via modulation of oxidative stress and mitochondrial cytochrome c (CytC), an effect to be better clarified. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…In contrast, Russo et al observed a 5 cm −1 upshift in the line at 1587 rel. cm −1 and used it to differentiate between healthy and apoptotic and pre-apoptotic brain cells of Mongolian gerbils, associating the line shift with cytochrome c deformation due to the protein binding to membrane elements [35]. A similar observation was reported earlier by Murgida and Hildebrandt [46,47], who saw a 10 cm −1 upshift in the line of the ν 19 vibration in ferrous compared to ferric cytochrome c adsorbed to a surface-enhanced Raman active substrate.…”
Section: Cytochrome-c-resonant Raman Spectra and Relative Raman Line supporting
confidence: 68%
See 1 more Smart Citation
“…In contrast, Russo et al observed a 5 cm −1 upshift in the line at 1587 rel. cm −1 and used it to differentiate between healthy and apoptotic and pre-apoptotic brain cells of Mongolian gerbils, associating the line shift with cytochrome c deformation due to the protein binding to membrane elements [35]. A similar observation was reported earlier by Murgida and Hildebrandt [46,47], who saw a 10 cm −1 upshift in the line of the ν 19 vibration in ferrous compared to ferric cytochrome c adsorbed to a surface-enhanced Raman active substrate.…”
Section: Cytochrome-c-resonant Raman Spectra and Relative Raman Line supporting
confidence: 68%
“…cm −1 , which at 532 nm excitation is one of the strongest Raman lines in ferrous cytochrome c, but is very weak if the protein is in ferric state. Recently, Russo et al used Raman microscopy with cytochrome-c-resonant excitation at 532 nm, using the redox state of cytochrome c as a crucial indicator for cell apoptosis [35], while Kakita et al used 532 nm excitation to quantify the redox state of cytochromes b and c in yeast [36]. Shin et al monitored photothermally induced mitochondrially mediated apoptosis in situ based on the Raman spectrum of cytochrome c, using surface-enhanced resonant Raman microscopy with gold nanoparticles and 785 nm excitation [37].…”
Section: Introductionmentioning
confidence: 99%
“…The most prominent peaks in correlation with vtx treatment are depicted in purple boxes in the loading plots. The peaks around 1308-1315 cm −1 , 1125 cm −1 and 747 cm −1 can be assigned to cytochrome c [28,38]. The bands in the region between 1447-1450 cm −1 are indicative of changes in the CH 2 conformation of proteins [30,31,39].…”
Section: Mitochondrial Spectra Identify Spectral Differences Between ...mentioning
confidence: 96%
“…The neuroprotective properties of insulin in ischemic injury have been studied for more than 30 years [ 164 , 165 , 166 , 167 ]. It has been shown that insulin with various delivery methods (subcutaneous, intraperitoneal, intravenous, and intracerebroventricular) positively affects the survival and cognitive functions of animals that have undergone cerebral ischemia [ 165 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 ]. The antiapoptotic signaling pathway, including IR/IRS/PI3K/AKT, plays a leading role in the implementation of the neuroprotective action of insulin.…”
Section: Intranasal Insulin and Brain Ischemiamentioning
confidence: 99%